Pre-lithiated silica composite material as well as preparation method and application thereof
Through disproportionation, CVD carbon coating and prelithiation of silicon oxygen materials, SiOx/Si@C/Li composite material is formed, which solves the problem of irreversible reaction of silicon oxygen materials during the first charging and discharging process in lithium-ion batteries, and achieves high efficiency Coulomb efficiency and stable cycle performance.
Patent Information
- Application Number
- CN202411646314.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-18
AI Technical Summary
The silicon oxygen material in lithium-ion batteries has an irreversible reaction during the first charge and discharge process, resulting in low initial Coulomb efficiency and volume expansion problems, limiting its application potential.
The silicon oxygen material is treated by three-step methods such as disproportionation, CVD carbon coating and prelithiation, and the SiOx/Si@C/Li composite material is formed to improve the structural stability and conductivity of the material.
It significantly improves the first-circle Coulomb efficiency and cycle stability of silicon oxygen materials, reduces volume expansion during charging and discharging, and improves electrochemical performance.
Smart Images

Figure CN119480999A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a pre-lithiation silicon-oxygen composite material and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries (LIBs) are a key component of modern energy storage technology, and the optimization of their performance is crucial to promote the development of the new energy industry. x ) materials are considered to be an ideal substitute for graphite due to their higher theoretical specific capacity. However, SiO x The material undergoes an irreversible reaction with lithium during the first charge and discharge process, generating byproducts such as Li2O and lithium silicate, resulting in a low initial Coulomb efficiency (ICE). x The material still faces this volume expansion problem, which limits its potential for practical applications.
[0003] To overcome these challenges, researchers have adopted a variety of strategies. For example, SiO x Although converting the material into pure silicon can improve the initial Coulombic efficiency, this method has been relatively less studied. At the same time, it also faces the problem of large volume expansion, which is not conducive to the cycle stability of the battery. Carbon coating technology is used to limit the volume expansion of the material and improve the conductivity of the material, but uniform coating of the material remains a challenge. x The researchers tried to improve the problem of low initial efficiency of the material by adding lithium supplements. The lithium supplement can promote the x The material undergoes lithiation during the first charge and discharge process, but the amount of lithium supplement added and the control of reaction conditions are difficult. In addition, the instability of the material and insufficient pre-lithiation lead to poor material uniformity. These problems require further research and resolution. Therefore, a synergistic strategy needs to be developed to improve SiO x Negative electrode materials can reduce the side reactions of the first cycle of silicon-oxygen materials and improve the first cycle coulomb efficiency and cycle stability of silicon-oxygen materials. x Application of materials in the field of lithium-ion batteries.
[0004] Patent publication number CN 112038598A discloses a pre-lithiated silicon oxide negative electrode material and its preparation method and application, comprising the following steps: (1) batching: obtaining silicon oxide negative powder, wherein the silicon oxide powder is silicon oxide powder that has not been disproportionated; obtaining lithium carbonate powder, wherein the lithium carbonate powder is analytically pure, anhydrous lithium carbonate powder; (2) mixing: adding the silicon oxide powder and the lithium carbonate powder into a mixer according to a certain ratio, stirring and mixing, to obtain a uniform mixed powder A; (3) heat treatment: subjecting the mixed powder A in step (2) to a heat treatment reaction under an inert gas to obtain an intermediate product B; (4) CVD carbon coating: subjecting the intermediate product B obtained in step (3) to carbon coating under a carbon source gas by a chemical deposition method, to obtain a pre-lithiated silicon oxide negative electrode material. In this patent, the amorphous silicon dioxide in silicon oxide is consumed in advance and fully reacted to generate a stable phase lithium silicate, thereby improving the first coulomb efficiency to a certain extent. However, there are still problems with material instability and insufficient pre-lithiation, so there is still room for improvement in the first coulombic efficiency and stability. Summary of the invention
[0005] In order to solve the technical problems of poor first coulombic efficiency and stability of pre-lithiated silicon oxide, the present invention proposes a pre-lithiated silicon-oxygen composite material and a preparation method and application thereof. Through a three-step method of disproportionation, CVD carbon coating and pre-lithiation process, the performance of silicon-oxygen material is effectively improved, especially the first coulombic efficiency and cycle stability of the battery are improved.
[0006] In order to achieve the above object, the technical solution of the present invention is achieved as follows:
[0007] (1) screening silicon oxide through a sieve with a specific mesh number to obtain silicon oxide with uniform particle size;
[0008] (2) placing the screened silicon oxide in a rotary tube atmosphere furnace and calcining it at high temperature in an inert gas environment to induce a disproportionation reaction of the silicon oxide to obtain SiO x / Si material;
[0009] (3) Cooling the calcined silicon-oxygen material to a suitable temperature, and performing a secondary high-temperature calcination (chemical vapor deposition CVD) in a mixed atmosphere of an inert gas and a carbon source gas to achieve carbon coating to obtain SiO x / Si@C composites;
[0010] (4) In a glove box, the carbon-coated silicon-oxygen material is mixed with a lithium supplement agent, and then transferred to a tube furnace connected to the glove box for high-temperature pre-lithiation treatment; the treated silicon-oxygen material is washed and dried to obtain a pre-lithiation silicon-oxygen composite material, i.e., SiO x / Si@C / Li composite materials.
[0011] The particle size of the silicon oxide is 13-48 μm.
[0012] The disproportionation reaction conditions are as follows: calcination temperature is 800-950° C., time is 1-3 hours, and heating rate is 2-10° C. / min.
[0013] The carbon coating conditions of the chemical vapor deposition (CVD) are as follows: the calcination temperature is 700-850° C. and the calcination time is 10-60 min.
[0014] The lithium supplement agent is one or more of lithium hydride, lithium hydroxide, lithium nitride, lithium oxalate, lithium fluoride, lithium nitrate and lithium powder.
[0015] The SiO x The mass ratio of the / Si@C composite material to the lithium supplement agent is 5-20:1.
[0016] The calcination temperature of the pre-lithiation treatment is 650-800° C. and the time is 1-6 hours.
[0017] The washing process needs to be performed with deionized water until the pH value is less than 9.
[0018] The inert gas used in the temperature rise and heat preservation stages of the disproportionation reaction, CVD carbon coating, and pre-lithiation treatment is argon or nitrogen.
[0019] The CVD heat preservation stage is a mixed gas of an inert gas and a carbon source gas, the inert gas is argon or nitrogen, the carbon source gas is acetylene, methane, toluene, and the volume flow ratio of the mixed gas is 1-10:1.
[0020] The above-mentioned pre-lithiation silicon-oxygen composite material is used in lithium batteries. The pre-lithiation silicon-oxygen composite material is used as an active material in an electrode sheet. The electrode sheet is prepared by mixing the pre-lithiation silicon-oxygen composite material, a conductive agent and a binder and then coating the mixture on a current collector.
[0021] The mass ratio of the pre-lithiation silicon-oxygen composite material, the conductive agent and the binder is (7-9.3): (0.3-2): (0.4-1).
[0022] The conductive agent is any one of acetylene black, Ketjen black, conductive graphite or SuperP.
[0023] The binder is styrene-butadiene rubber, sodium carboxymethyl cellulose or polyacrylic acid.
[0024] Preferably, the binder includes carboxymethyl cellulose, and styrene-butadiene rubber emulsion or polyacrylic acid; the mass ratio of carboxymethyl cellulose to styrene-butadiene rubber emulsion or polyacrylic acid is 2:3.
[0025] In the battery, the electrode sheet is the negative electrode, the lithium sheet is the positive electrode, 500 μL of electrolyte is added to each of the electrode sheet and the lithium sheet, and a diaphragm is provided between the electrode sheet and the lithium sheet; the discharge voltage of the charge and discharge cycle test is 0.01-2V, and the current density is 0.1C-1C.
[0026] The electrolyte used for battery assembly: solute: lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), etc.
[0027] The solvent is carbonates such as dimethyl carbonate (DMC), ethylene carbonate (EC), ethyl methyl carbonate (EMC), and ethers such as ethylene glycol dimethyl ether (DME).
[0028] Additives: vinylene carbonate (VC) and fluoroethylene carbonate (FEC).
[0029] Preferably, the electrolyte is LiPF6+ (EC / DEC=1:1, v / v).
[0030] Beneficial effects of the present invention: The present invention significantly improves the performance of silicon-oxygen composite materials through the synergistic effect of the three-step process of disproportionation, CVD carbon coating and pre-lithiation. It has the following three advantages: the disproportionation reaction consumes part of SiO x The internal silicon-oxygen region increases the Si phase content inside the silicon-oxygen to form a dense SiO x The structure lays the foundation for the subsequent carbon coating and pre-lithiation process; the carbon coating layer formed by CVD technology effectively reduces the SiO x The interaction between carbon coating and disproportionation process further alleviates the SiO x In the subsequent high-temperature pre-lithiation process, the internal grains of the material increase, thereby alleviating the volume expansion problem during the charge and discharge process. In addition, the carbon coating layer also reduces the occurrence of interfacial side reactions and increases the stability of the solid electrolyte interface (SEI) film. Since the carbon source is in the gas phase, the uniformity of the carbon coating is ensured, thereby improving the conductivity and structural stability of the material. In addition, in the pre-lithiation process, the carbon coating layer makes SiO x The reaction between the lithium supplement and the SiO2 becomes mild, and the rough surface of the carbon coating increases the interaction between the lithium supplement and the SiO2 x The contact area of the reaction improves the uniformity of pre-lithiation, which leads to a higher content and crystallinity of the Li2Si2O5 phase in the pre-lithiation product. The use of lithium supplements for pre-lithiation can consume part of the oxygen, form lithium silicate phase in advance, reduce the irreversible reaction during the first charge, and enhance the carbon layer and SiO x In addition, the dense SiO xThe synergistic effect of these three steps effectively reduces the side reactions of silicon-oxygen materials in the first cycle, improves the first cycle Coulombic efficiency, and alleviates the volume expansion during the cycle, thereby significantly improving the SiO x The electrochemical performance of the material is that the first-cycle coulomb efficiency of the pre-lithiation silicon-oxygen composite material prepared by the present invention can reach 90.59%. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1 This is a schematic diagram of the structure of the product prepared in Example 1.
[0033] Figure 2 Silicon Oxide SiO x Comparative Example 1: SiO x / Si and Comparative Example 2: SiO x / Si@C product’s XRD pattern.
[0034] Figure 3 Silicon Oxide SiO x Comparative Example 3: SiO x @C XRD pattern of the product.
[0035] Figure 4 For the SiO x / Si@C / Li-5%, SiO in Example 1 x / Si@C / Li-10% and SiO x / Si@C / Li-20% product.
[0036] Figure 5 is the SEM image of the product, ac is the SiO x / Si@C; dg is SiO in Example 1 x / Si@C / Li-10%, the corresponding EDS graph is on the lower right. DETAILED DESCRIPTION
[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] Example 1
[0039] A pre-lithiation silicon-oxygen composite material, Figure 1 The structural diagram of the preparation process is as follows: SiO x A disproportionation reaction occurs at high temperature to generate a certain amount of Si, and then a carbon coating layer is formed by CVD, and finally a lithium-containing compound is added for pre-lithiation to generate lithium silicate. The preparation method specifically includes the following steps:
[0040] Step 1: Screening SiO x Particles: Weigh SiO x 10g of particles were sieved with 300-mesh and 1000-mesh sieves to separate SiO2 with a particle size of 13 to 48 μm. x Granulate to obtain product A.
[0041] Step 2: Disproportionation reaction and CVD carbon coating: Product A is placed in a quartz furnace tube, and then a rotary tube atmosphere furnace is assembled. The temperature is raised to 400°C at a heating rate of 10°C / min under an argon atmosphere, and then raised to 900°C at a heating rate of 5°C / min, and kept warm for 2 hours. The argon flow rate is set to 100sccm. After the insulation is completed, the temperature is reduced to 800°C at a cooling rate of 10°C / min. After the temperature drops to 800°C, a mixed gas of argon (100sccm) and acetylene (10sccm) with a volume ratio of 10:1 is introduced, and the carbon coating is carried out at 800°C for 30 minutes, and then the acetylene gas is stopped. Naturally cool to room temperature under an argon atmosphere to obtain product B, i.e., SiO x / Si@C composite materials.
[0042] Step 3: Pre-lithiation: According to the mass ratio of product to lithium hydride of 10:1, 5g of product B and 0.5g of lithium hydride were weighed in a glove box filled with argon atmosphere, and the mixture was quickly dispersed evenly in a degassing machine. The instrument was run for 5 minutes, and the dispersed mixture was placed in a tubular furnace connected to the glove box, and the temperature was raised to 400°C at a heating rate of 10°C / min, and then raised to 700°C at a heating rate of 5°C / min, and kept warm for 2h. After the heating was completed, the program was stopped, and the product was taken out when the temperature dropped to room temperature. The product was filtered and washed with deionized water until the pH was 8, and then placed in a vacuum dryer at 80°C for 12h to obtain a dry product C, i.e., the pre-lithiation product SiO x / Si@C / Li-10%.
[0043] Step 4: Prepare electrode sheet: Prepare product C: SiO x / Si@C / Li-10% composite material was mixed with conductive agent (Super P), adhesive (sodium carboxymethyl cellulose CMC) and binder (styrene-butadiene latex SBR) in a mass ratio of 8:1:0.4:0.6. The mixture was ball-milled to form a slurry. The slurry was evenly coated on the copper foil with a coating machine. It was dried at 100°C in a vacuum drying oven for 12 hours to form an electrode sheet.
[0044] Step 5: Assemble the battery and test: Assemble the prepared electrode sheets into lithium-ion half-cells. Use a BlueDian electrochemical workstation to perform constant current charge and discharge tests with a test voltage range of 0.01V-2.0V. Assemble the resulting material into a button cell and test its performance as a negative electrode material for lithium-ion batteries.
[0045] Example 2
[0046] A pre-lithiation silicon-oxygen composite material, the preparation method specifically comprises the following steps:
[0047] Step 1: Screening SiO x Particles: Weigh SiO x 10g of particles were sieved with 300-mesh and 1000-mesh sieves to separate SiO2 with a particle size of 13 to 48 μm. x Granulate to obtain product A.
[0048] Step 2: Disproportionation reaction and CVD carbon coating: Product A is placed in a quartz furnace tube, and then a rotary tube atmosphere furnace is assembled. The temperature is raised to 300°C at a heating rate of 5°C / min under an argon atmosphere, and then raised to 950°C at a heating rate of 10°C / min, and kept warm for 1h. The argon flow rate is set to 100sccm. After the insulation is completed, the temperature is lowered to 700°C at a cooling rate of 10°C / min. After the temperature drops to 700°C, a mixed gas of argon (100sccm) and methane (20sccm) with a volume ratio of 5:1 is introduced, and the mixture is kept at 700°C for 60 minutes for carbon coating, and then the introduction of methane gas is stopped. Naturally cool to room temperature under an argon atmosphere to obtain product B, i.e., SiO x / Si@C composite materials.
[0049] Step 3: Pre-lithiation: According to the mass ratio of product to lithium hydride of 16:1, 4.5g of product B and 0.3g of lithium hydride were weighed in a glove box filled with argon atmosphere, and the mixture was quickly dispersed evenly in a degassing machine. The instrument was run for 5 minutes, and the dispersed mixture was placed in a tubular furnace connected to the glove box, and the temperature was raised to 400°C at a heating rate of 10°C / min, and then raised to 700°C at a heating rate of 5°C / min, and kept warm for 2h. After the heating was completed, the program was stopped, and the product was taken out when the temperature dropped to room temperature. The product was filtered and washed with deionized water until the pH was 8, and then placed in a vacuum dryer at 80°C for 12h to obtain a dry product C, i.e., the pre-lithiation product SiO x / Si@C / Li-6%.
[0050] Example 3
[0051] A pre-lithiation silicon-oxygen composite material, the preparation method specifically comprises the following steps:
[0052] Step 1: Screening SiO x Particles: Weigh SiO x 10g of particles were sieved with 300-mesh and 1000-mesh sieves to separate SiO2 with a particle size of 13 to 48 μm. x Granulate to obtain product A.
[0053] Step 2: Disproportionation reaction and CVD carbon coating: Product A is placed in a quartz furnace tube, and then a rotary tube atmosphere furnace is assembled. The temperature is raised to 500°C at a heating rate of 10°C / min under an argon atmosphere, and then raised to 800°C at a heating rate of 2°C / min, and kept warm for 3 hours. The argon flow rate is set to 100 sccm. After the insulation is completed, the temperature is raised to 850°C at a heating rate of 2°C / min, and a mixed gas of argon (100 sccm) and acetylene (10 sccm) with a volume ratio of 10:1 is introduced. The mixture is kept at 850°C for 10 minutes for carbon coating, and then the acetylene gas is stopped. Naturally cool to room temperature under an argon atmosphere to obtain product B, i.e., SiO x / Si@C composite materials.
[0054] Step 3: Pre-lithiation: According to the mass ratio of product to lithium hydride of 10:1, 5g of product B and 0.5g of lithium hydride were weighed in a glove box filled with argon atmosphere, and the mixture was quickly dispersed evenly in a degassing machine. The instrument was run for 5 minutes, and the dispersed mixture was placed in a tubular furnace connected to the glove box, and the temperature was raised to 400°C at a heating rate of 10°C / min, and then raised to 800°C at a heating rate of 5°C / min, and kept warm for 1h. After the heating was completed, the program was stopped, and the product was taken out when the temperature dropped to room temperature. The product was filtered and washed with deionized water until the pH was 8, and then placed in a vacuum dryer at 80°C for 12h to obtain a dry product C, i.e., the pre-lithiation product SiO x / Si@C / Li-10%.
[0055] Example 4
[0056] A pre-lithiation silicon-oxygen composite material, the preparation method specifically comprises the following steps:
[0057] Step 1: Screening SiO x Particles: Weigh SiO x 10g of particles were sieved with 300-mesh and 1000-mesh sieves to separate SiO2 with a particle size of 13 to 48 μm. x Granulate to obtain product A.
[0058] Step 2: Disproportionation reaction and CVD carbon coating: Product A is placed in a quartz furnace tube, and then a rotary tube atmosphere furnace is assembled. The temperature is raised to 400°C at a heating rate of 10°C / min in a nitrogen atmosphere, and then raised to 900°C at a heating rate of 5°C / min, and kept warm for 3 hours. The nitrogen flow rate is set to 100 sccm. After the insulation is completed, the temperature is lowered to 800°C at a cooling rate of 10°C / min. After the temperature drops to 800°C, a mixed gas of argon (50 sccm) and acetylene (50 sccm) with a volume ratio of 1:1 is introduced, and the carbon coating is carried out at 800°C for 30 minutes, and then the acetylene gas is stopped. Naturally cool to room temperature in an argon atmosphere to obtain product B, i.e., SiO x / Si@C composite materials.
[0059] Step 3: Pre-lithiation: According to the mass ratio of product to lithium hydride of 5:1, 5g of product B and 1g of lithium nitride were weighed in a glove box filled with argon atmosphere, and the mixture was quickly dispersed evenly in a degassing machine. The instrument was run for 5 minutes, and the dispersed mixture was placed in a tubular furnace connected to the glove box, and the temperature was raised to 400°C at a heating rate of 10°C / min, and then raised to 650°C at a heating rate of 5°C / min, and kept warm for 6h. After the heating was completed, the program was stopped, and the product was taken out when the temperature dropped to room temperature. The product was filtered and washed with deionized water until the pH was 8, and then placed in a vacuum dryer at 80°C for 12h to obtain a dry product C, i.e., the pre-lithiation product SiO x / Si@C / Li-20%.
[0060] Example 5
[0061] A pre-lithiation silicon-oxygen composite material, the preparation method specifically comprises the following steps:
[0062] Step 1: Screening SiO x Particles: Weigh SiO x 10g of particles were sieved with 300-mesh and 1000-mesh sieves to separate SiO2 with a particle size of 13 to 48 μm. x Granulate to obtain product A.
[0063] Step 2: Disproportionation reaction and CVD carbon coating: Product A is placed in a quartz furnace tube, and then a rotary tube atmosphere furnace is assembled. The temperature is raised to 400°C at a heating rate of 10°C / min under an argon atmosphere, and then raised to 850°C at a heating rate of 5°C / min, and kept warm for 2 hours. The argon flow rate is set to 100 sccm. After the insulation is completed, a mixed gas of argon (100 sccm) and toluene (10 sccm) with a volume ratio of 10:1 is introduced, and the carbon coating is carried out at 800°C for 30 minutes, and then the toluene gas is stopped. Naturally cool to room temperature under an argon atmosphere to obtain product B, i.e., SiO x / Si@C composite materials.
[0064] Step 3: Pre-lithiation: According to the mass ratio of product to lithium hydride of 10:1, 5g of product B and 0.5g of lithium powder were weighed in a glove box filled with argon atmosphere, and the mixture was quickly dispersed evenly in a degassing machine. The instrument was run for 5 minutes, and the dispersed mixture was placed in a tubular furnace connected to the glove box, and the temperature was increased to 400°C at a heating rate of 10°C / min, and then increased to 700°C at a heating rate of 5°C / min, and kept warm for 2h. After the heating was completed, the program was stopped, and the product was taken out when the temperature dropped to room temperature. The product was filtered and washed with deionized water until the pH was 8, and then placed in a vacuum dryer at 80°C for 12h to obtain a dry product C, i.e., the pre-lithiation product SiO x / Si@C / Li-10%.
[0065] Comparative Example 1
[0066] Step 1: Screening SiO x Particles: Weigh SiO x 10g of particles were sieved with 300-mesh and 1000-mesh sieves to separate SiO2 with a particle size of 13 to 48 μm. x Granulate to obtain product A.
[0067] Step 2: Disproportionation reaction: Product A is placed in a quartz furnace tube, and then a rotary tube atmosphere furnace is assembled. The temperature is raised to 400°C at a heating rate of 10°C / min in an argon atmosphere, and then raised to 900°C at a heating rate of 5°C / min. The temperature is kept at this temperature for 2 hours, and the argon flow rate is set to 100 sccm. After the temperature is kept at this temperature, the program is stopped, and the product is taken out when the temperature drops to room temperature to obtain product B, i.e., the disproportionated silicon-oxygen material (SiO x / Si).
[0068] Comparative Example 2
[0069] Step 1: Screening SiO x Particles: Weigh SiO x 10g of particles were sieved with 300-mesh and 1000-mesh sieves to separate SiO2 with a particle size of 13 to 48 μm. x Granulate to obtain product A.
[0070] Step 2: Disproportionation reaction and CVD carbon coating: Product A is placed in a quartz furnace tube, and then a rotary tube atmosphere furnace is assembled. The temperature is raised to 400°C at a heating rate of 10°C / min under an argon atmosphere, and then raised to 900°C at a heating rate of 5°C / min, and kept warm for 2 hours. The argon flow rate is set to 100sccm. After the insulation is completed, the temperature is reduced to 800°C at a cooling rate of 10°C / min. After the temperature drops to 800°C, a mixed gas of argon (100sccm) and acetylene (10sccm) with a volume ratio of 10:1 is introduced, and the carbon coating is carried out at 800°C for 30 minutes, and then the acetylene gas is stopped. Naturally cool to room temperature under an argon atmosphere to obtain product B, i.e., SiO x / Si@C composite materials.
[0071] Comparative Example 3
[0072] Step 1: Screening SiO x Particles: Weigh SiO x 10g of particles were sieved with 300-mesh and 1000-mesh sieves to separate SiO2 with a particle size of 13 to 48 μm. x Granulate to obtain product A.
[0073] Step 2: CVD carbon coating: Product A is placed in a quartz furnace tube, and then a rotary tube atmosphere furnace is assembled. The temperature is raised to 800°C at a heating rate of 10°C / min in an argon atmosphere. After the temperature reaches 800°C, a mixed gas of argon (100 sccm) and acetylene (10 sccm) with a volume ratio of 10:1 is introduced, and the temperature is kept at 800°C for 30 minutes for carbon coating, and then the introduction of acetylene gas is stopped. The mixture is naturally cooled to room temperature in an argon atmosphere to obtain product B, i.e., SiO x @CComposite materials.
[0074] Comparative Example 4
[0075] A pre-lithiation silicon-oxygen composite material, the preparation method specifically comprises the following steps:
[0076] Step 1: Disproportionation reaction and CVD carbon coating: Unscreened SiO xThe powder was placed in a quartz furnace tube, and then a rotary tube atmosphere furnace was assembled. The temperature was raised to 400°C at a heating rate of 10°C / min in an argon atmosphere, and then raised to 900°C at a heating rate of 5°C / min, and kept at this temperature for 2 hours. The argon flow rate was set to 100 sccm. After the insulation, the temperature was lowered to 800°C at a cooling rate of 10°C / min. After the temperature dropped to 800°C, a mixed gas of argon (100 sccm) and acetylene (10 sccm) with a volume ratio of 10:1 was introduced, and the mixture was kept at 800°C for 30 minutes for carbon coating, and then the acetylene gas was stopped. The mixture was naturally cooled to room temperature in an argon atmosphere to obtain product A, i.e., SiO x / Si@C composite materials.
[0077] Step 2: Pre-lithiation: According to the mass ratio of product to lithium hydroxide of 10:1, 5g of product B and 0.5g of lithium hydroxide were weighed in a glove box filled with argon atmosphere, and the mixture was quickly dispersed evenly in a degassing machine. The instrument was run for 5 minutes, and the dispersed mixture was placed in a tubular furnace connected to the glove box, and the temperature was increased to 400°C at a heating rate of 10°C / min, and then increased to 700°C at a heating rate of 5°C / min, and kept warm for 2h. After the heating was completed, the program was stopped, and the product was taken out when the temperature dropped to room temperature. The product was filtered and washed with deionized water until the pH was 8, and then placed in a vacuum dryer at 80°C for 12h to obtain a dry product C, i.e., the pre-lithiation product SiO x / Si@C / Li-10%.
[0078] Comparative Example 5
[0079] Step 1: Screening SiO x Particles: Weigh SiO x 10g of particles were sieved with 300-mesh and 1000-mesh sieves to separate SiO2 with a particle size of 13 to 48 μm. x Granulate to obtain product A.
[0080] Step 2: Disproportionation reaction and CVD carbon coating: Product A is placed in a quartz furnace tube, and then a rotary tube atmosphere furnace is assembled. The temperature is raised to 700°C at a heating rate of 10°C / min in an argon atmosphere, and the temperature is kept for 0.5h. The argon flow rate is set to 100sccm. After the insulation is completed, the temperature is raised to 800°C at a heating rate of 10°C / min, and a mixed gas of argon (100sccm) and acetylene (10sccm) with a volume ratio of 10:1 is introduced. The mixture is kept at 800°C for 30 minutes for carbon coating, and then the acetylene gas is stopped. Naturally cool to room temperature in an argon atmosphere to obtain product B, i.e., SiO x / Si@C composite materials.
[0081] Step 3: Pre-lithiation: According to the mass ratio of product to lithium oxalate of 10:1, 5g of product B and 0.5g of lithium oxalate were weighed in a glove box filled with argon atmosphere, and the mixture was quickly dispersed evenly in a degassing machine. The instrument was run for 10 minutes, and the dispersed mixture was placed in a tube furnace connected to the glove box, and the temperature was increased to 400°C at a heating rate of 10°C / min, and then increased to 700°C at a heating rate of 5°C / min, and kept warm for 2h. After the heating was completed, the program was stopped, and the product was taken out when the temperature dropped to room temperature. The product was filtered and washed with deionized water until the pH was 8, and then placed in a vacuum dryer at 80°C for 12h to obtain a dry product C, i.e., the pre-lithiation product SiO x / Si@C / Li-10%.
[0082] Comparative Example 6
[0083] Step 1: Screening SiO x Particles: Weigh SiO x 10g of particles were sieved with 300-mesh and 1000-mesh sieves to separate SiO2 with a particle size of 13 to 48 μm. x Granulate to obtain product A.
[0084] Step 2: Disproportionation reaction: Product A is placed in a tube furnace, and an argon atmosphere is introduced. The temperature is raised to 400°C at a rate of 10°C / min, and then raised to 900°C at a rate of 5°C / min. The temperature is kept at this temperature for 2 hours, and the argon flow rate is set to 100 sccm. After the temperature is kept at this temperature, the program is stopped, and the product is taken out when the temperature drops to room temperature to obtain product B, i.e., the disproportionated silicon-oxygen material (SiO x / Si).
[0085] Step 3: CVD carbon coating: Product B is placed in a quartz furnace tube, and then a rotary tube atmosphere furnace is assembled. It is heated to 600°C at a heating rate of 15°C / min in an argon atmosphere, and the argon flow rate is 100sccm. After the temperature rises to 600°C, a mixed gas of argon (200sccm) and acetylene (10sccm) with a volume ratio of 20:1 is introduced, and the mixture is kept at 700°C for 10 minutes for carbon coating, and then the introduction of acetylene gas is stopped. Naturally cool to room temperature in an argon atmosphere to obtain product C, i.e., SiO x / Si@C composite materials.
[0086] Step 4: Pre-lithiation: According to the mass ratio of product to lithium powder of 10:1, 5g of product B and 0.5g of lithium powder were weighed in a glove box filled with argon atmosphere, and the mixture was quickly dispersed evenly in a degassing machine. The instrument was run for 5 minutes, and the dispersed mixture was placed in a tubular furnace connected to the glove box, and the temperature was increased to 400°C at a heating rate of 10°C / min, and then increased to 700°C at a heating rate of 5°C / min, and kept warm for 2h. After the heating was completed, the program was stopped, and the product was taken out when the temperature dropped to room temperature. The product was filtered and washed with deionized water until the pH was 8, and then placed in a vacuum dryer at 80°C for 12h to obtain a dry product C, i.e., the pre-lithiation product SiO x / Si@C / Li-10%.
[0087] Comparative Example 7
[0088] Step 1: Screening SiO x Particles: Weigh SiO x 10g of particles were sieved with 300-mesh and 1000-mesh sieves to separate SiO2 with a particle size of 13 to 48 μm. x Granulate to obtain product A.
[0089] Step 2: Disproportionation reaction and CVD carbon coating: Product A is placed in a quartz furnace tube, and then a rotary tube atmosphere furnace is assembled. The temperature is raised to 400°C at a heating rate of 10°C / min under an argon atmosphere, and then raised to 900°C at a heating rate of 5°C / min, and kept warm for 2 hours. The argon flow rate is set to 100sccm. After the insulation is completed, the temperature is reduced to 800°C at a cooling rate of 10°C / min. After the temperature drops to 800°C, a mixed gas of argon (100sccm) and acetylene (10sccm) with a volume ratio of 10:1 is introduced, and the carbon coating is carried out at 800°C for 30 minutes, and then the acetylene gas is stopped. Naturally cool to room temperature under an argon atmosphere to obtain product B, i.e., SiO x / Si@C composite materials.
[0090] Step 3: Pre-lithiation: According to the mass ratio of product to lithium fluoride of 20:1, 5g of product B and 0.2g of lithium fluoride were weighed in a glove box filled with argon atmosphere, and the mixture was quickly dispersed evenly in a degassing machine. The instrument was run for 10 minutes, and the dispersed mixture was placed in a tubular furnace connected to the glove box, and an argon atmosphere was introduced. The temperature was raised to 650°C at a rate of 10°C / min, and the temperature was kept for 30 minutes. After the heating was completed, the program was stopped, and the product was taken out when the temperature dropped to room temperature. The product was filtered and washed with deionized water until the pH was 8, and then placed in a vacuum dryer at 80°C for 12 hours to obtain product C, that is, the pre-lithiation product SiO x / Si@C / Li-5%.
[0091] Comparative Example 8
[0092] Step 1: Screening SiO x Particles: Weigh SiO x 10g of granules were screened with a 300-1000 mesh screen to separate out 13-48μm SiO x Granulate to obtain product A.
[0093] Step 2: Disproportionation reaction and CVD carbon coating: Product A is placed in a quartz furnace tube, and then a rotary tube atmosphere furnace is assembled. The temperature is raised to 400°C at a heating rate of 10°C / min in an argon atmosphere, and then raised to 950°C at a heating rate of 5°C / min, and kept warm for 3 hours. The argon flow rate is set to 100sccm. After the insulation is completed, the temperature is lowered to 850°C at a cooling rate of 10°C / min. After the temperature drops to 850°C, a mixed gas of argon (50sccm) and acetylene (10sccm) with a volume ratio of 5:1 is introduced, and the mixture is kept warm at 850°C for 1 hour for carbon coating, and then the acetylene gas is stopped. Naturally cool to room temperature in an argon atmosphere to obtain product B, i.e., SiO x / Si@C composite materials.
[0094] Step 3: Pre-lithiation: According to the mass ratio of product to lithium nitrate of 5:1, 5g of product B and 2g of lithium nitrate were weighed in a glove box filled with argon atmosphere, and the mixture was quickly dispersed evenly in a degassing machine. The instrument was run for 5 minutes, and the dispersed mixture was placed in a tubular furnace connected to the glove box, and an argon atmosphere was introduced. The temperature was raised to 800°C at a rate of 5°C / min, and the temperature was kept for 5 hours. After the heating was completed, the program was stopped, and the product was taken out when the temperature dropped to room temperature. The product was filtered and washed with deionized water until the pH was 8, and then placed in a vacuum dryer at 80°C for 12 hours to obtain a dry product C, i.e., the pre-lithiation product SiO x / Si@C / Li-20%.
[0095] Comparative Example 9
[0096] Step 1: Screening SiO x Particles: Weigh SiO x 10g of particles were sieved with 300-mesh and 1000-mesh sieves to separate SiO2 with a particle size of 13 to 48 μm. x Granulate to obtain product A.
[0097] Step 2: Disproportionation reaction: Product A was placed in a quartz furnace tube, and then a rotary tube atmosphere furnace was assembled. The temperature was raised to 400°C at a rate of 10°C / min under an argon atmosphere, and then raised to 900°C at a rate of 5°C / min, and kept at this temperature for 2 hours. The argon flow rate was set to 100 sccm. Then, the product was naturally cooled to room temperature under an argon atmosphere to obtain product B, i.e., SiO x / Si material.
[0098] Step 3: pre-lithiation and CVD carbon coating: according to the mass ratio of product to lithium hydride of 10:1, 5g of product B and 0.5g of lithium hydride were weighed in a glove box filled with argon atmosphere, and put into a degassing machine for rapid and uniform dispersion. The instrument was run for 5 minutes, and the dispersed mixture was placed in a tubular furnace connected to the glove box, and the temperature was increased to 400°C at a heating rate of 10°C / min, and then increased to 700°C at a heating rate of 5°C / min, and kept warm for 2h. After the insulation, the temperature was increased to 800°C at a heating rate of 5°C / min. After the temperature reached 800°C, a mixed gas of argon (100sccm) and acetylene (10sccm) with a volume ratio of 10:1 was introduced, and the mixture was kept warm at 800°C for 30 minutes for carbon coating, and then the introduction of acetylene gas was stopped. Then, the product was naturally cooled to room temperature under an argon atmosphere, and filtered and washed with deionized water until the pH value was 8, and then placed in a vacuum dryer at 80°C for 12 h to obtain a dry product C, i.e., the carbon-coated product SiO after pre-lithiation. x / Si / Li-10%@C.
[0099] The final prepared materials of Comparative Examples 1-9 and the raw material silicon oxide SiO x Electrode sheets were prepared according to the electrode sheet preparation steps in Example 1, and assembled into batteries for testing.
[0100] Figure 2 Silicon Oxide SiO x Comparative Example 1: SiO x / Si and Comparative Example 2: SiO x / Si@C product. The presence of SiO x The diffraction peak of Si appears after the disproportionation reaction, which proves that the disproportionation reaction occurs at 900℃.
[0101] Figure 3 Silicon Oxide SiO x Comparative Example 3: SiO x @C XRD diagram of the product. The diffraction peaks are similar, proving that carbon coating does not destroy the phase.
[0102] Figure 4 For the SiO x / Si@C / Li-5%, SiO in Example 1 x / Si@C / Li-10% and SiO x XRD pattern of / Si@C / Li-20% product. It is found that lithium silicate phase appears after the pre-lithiation reaction, among which the main phases are Li2SiO3 and Li2Si2O5.
[0103] Figure 5 For the SiO in Comparative Example 2 x / Si@C, SiO in Example 1 x / Si@C / Li-10% product SEM image. It was found that the particle size did not change significantly, and EDS analysis showed that the three elements Si, O, and C were evenly distributed, and the C element was concentrated on the particle surface, proving the presence of a carbon coating.
[0104] Table 1: Raw material silicon oxide SiO at 0.1C current density in the first cycle x Comparative Example 1: SiO x / Si, Comparative Example 2: SiO x / Si@C, Comparative Example 3: SiO x @C, Comparative Example 4: SiO x / Si@C / Li-10%, Comparative Example 5: SiO x / Si@C / Li-10%, Comparative Example 6: SiO x / Si@C / Li-10%, Comparative Example 7: SiO x / Si@C / Li-5%, Comparative Example 8: SiO x / Si@C / Li-20%, Comparative Example 9:
[0105] SiO x / Si / Li-10%@C, Example 1: SiO x Electrochemical performance of / Si@C / Li-10% materials
[0106]
[0107]
[0108] In Comparative Example 4, due to the lack of screening, SiO x The particles are uneven, the particles generated by the disproportionation reaction are of different sizes, and the CVD carbon coating is uneven; in Comparative Example 5, the heating rate of the disproportionation reaction is increased, the temperature is reduced, and the insulation is shortened, resulting in insufficient disproportionation reaction, uneven distribution of silicon crystal area and silicon oxygen area, and the silicon crystal area is mainly distributed outside, resulting in poor cycle performance; in Comparative Example 6, the heating rate of CVD carbon coating is too fast, the temperature is reduced, and the carbon coating time is reduced, resulting in uneven and thin carbon coating; in Comparative Example 7, the pre-lithium amount is 5%, the pre-lithium temperature is low, and the pre-lithium time is short, and the product pre-lithium is uneven; in Comparative Example 8, the disproportionation temperature is high, the time is long, the CVD temperature is high, the time is long, the pre-lithium temperature is high, the pre-lithium amount is high, and the time is long, which also leads to reduced performance; in Comparative Example 9, pre-lithium is first pre-lithium and then CVD carbon coating is used. In the absence of a carbon layer, the lithium supplement will directly react with SiO x react to form lithium silicates, which destroy SiO x In contrast, if a carbon layer is present, SiO xThe reaction with LiH will be milder, thus improving the uniformity of the pre-lithiation process. In addition, the formed lithium silicate phase helps to strengthen the SiO x The combination with LiH and carbon coating reduces the occurrence of irreversible reactions.
[0109] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a pre-lithiated silicon-oxygen composite material, characterized in that: The following steps are involved: (1) Calcine silicon oxide at high temperature to induce disproportionation reaction of silicon oxide to generate SiO x / Si material; (2) SiO x / Si material is carbon coated by chemical vapor deposition to form SiO x / Si@C composites; (3) SiO x The Si@C / Si@C composite material is mixed with a lithium supplement agent and then subjected to a pre-lithiation treatment to obtain a pre-lithiation silicon-oxygen composite material.
2. The method for preparing the pre-lithiated silicon-oxygen composite material according to claim 1, characterized in that: The particle size of the silicon oxide is 13-48 μm.
3. The method for preparing the pre-lithiation silicon-oxygen composite material according to claim 2, characterized in that: The conditions for high temperature calcination in step (1) are: temperature of 800-950° C., time of 1-3 h, and atmosphere of argon or nitrogen.
4. The method for preparing the pre-lithiation silicon-oxygen composite material according to claim 3, characterized in that: The conditions of the chemical vapor deposition are: temperature of 700-850° C., time of 10-60 min, and carbon source gas of acetylene, methane or toluene.
5. The method for preparing the pre-lithiated silicon-oxygen composite material according to claim 4, characterized in that: The lithium supplement agent is one or more of lithium hydride, lithium hydroxide, lithium nitride, lithium oxalate, lithium fluoride, lithium nitrate, and lithium powder; the SiO x The mass ratio of / Si@C composite material to lithium supplement agent is (5-20):
1.
6. The method for preparing the pre-lithiation silicon-oxygen composite material according to claim 5, characterized in that: The temperature of the pre-lithiation treatment is 650-800° C., the time is 1-6 hours, and the atmosphere is argon or nitrogen.
7. A pre-lithiated silicon-oxygen composite material prepared by the method according to any one of claims 1 to 6.
8. Use of the pre-lithiated silicon-oxygen composite material according to claim 7 in a lithium battery, characterized in that: The pre-lithiation silicon-oxygen composite material is used as an active material in an electrode sheet, and the electrode sheet is prepared by mixing the pre-lithiation silicon-oxygen composite material, a conductive agent and a binder and then coating the mixture on a current collector.
9. The use of the pre-lithiated silicon-oxygen composite material in a lithium battery according to claim 8, characterized in that: The mass ratio of the double carbon-coated silicon-oxygen material, the conductive agent and the binder is (7-9.3): (0.3-2): (0.4-1).
10. The use of the pre-lithiated silicon-oxygen composite material in a lithium battery according to claim 9, characterized in that: The conductive agent is any one of acetylene black, Ketjen black, conductive graphite or Super P; the binder is any one of styrene-butadiene rubber, sodium carboxymethyl cellulose or polyacrylic acid.
Citation Information
Patent Citations
Pre-lithiated silicon monoxide negative electrode material as well as preparation method and application thereof
CN112038598A